A possible role for reactive oxygen species in the regulation of an ultradian rhythm in Paramecium. Issue 6 (2nd November 2019) - Hinrichsen, Robert; Hawsawi, Ohuod
ABSTRACT: Reactive oxygen species (ROS) are essential for the viability of cells, while excess levels can be lethal by damaging proteins and nucleic acids. It is imperative to identify and elucidate the various cellular functions for which ROS molecules have a role. In this paper, the role of ROS in the regulation of ultradian rhythms in the ciliated protozoan Paramecium tetraurelia is examined. The frequency of spontaneous behavioral responses in Parameciun display a well-established ultradian rhythm with a periodicity of approximately 50–60 min. The artificial elevation of cytoplasmic ROS concentrations is shown to completely eliminate the rhythm in a reversible manner. Furthermore, the use of RNA interference techniques to knockdown the expression of superoxide dismutase, an enzyme that scavenges excess cytoplasmic ROS, also eliminates the ultradian rhythm. These data indicate that the concentration of ROS plays a role in the generation of the ultradian rhythm. A hypothesis is proposed for the generation of this ultradian rhythm that incorporates a role for ROS.